Project-Based Learning in Improving Early Childhood Children’s Ability to Know Social and Geographical Environments - Sri Setyowati; Nur Ika Sari Rakhmawati; Ruqoyyah Fitri; Wulan Patria Saroinsong; Nurhenti Dorlina Simatupang (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
The teacher's efforts in providing educational services in schools to introduce children's social and geographical environment can be made using project-based learning (Project Based Learn). This study aimed to determine the effectiveness of project-based learning in improving early children's skills in social and geographic environments. The research design used is a quasi-experimental design. The experimental group was not randomly selected, and the control group was separated into two sample groups. According to the hypothesis, the experiment produced substantial results. So that Ha is accepted, it can be concluded that project-based learning significantly influences the introduction of early childhood's social and geographical environment.